Improved Exercise-Related Skeletal Muscle Oxygen Consumption Following Uptake of Endurance Training Measured Using Near-Infrared Spectroscopy - Jones, Siana; D'Silva, Andrew; Bhuva, Anish; Lloyd, Guy; Manisty, Charlotte; Moon, James C.; Sharma, Sanjay; Hughes, Alun D. (Frontiers in Physiology, 2017)
Skeletal muscle metabolic function is known to respond positively to exercise interventions. Developing non-invasive techniques that quantify metabolic adaptations and identifying interventions that impart successful response are ongoing challenges for research. Healthy non-athletic adults (18-35 years old) were enrolled in a study investigating physiological adaptations to a minimum of 16 weeks endurance training prior to undertaking their first marathon. Before beginning training, participants underwent measurements of skeletal muscle oxygen consumption using near-infrared spectroscopy (NIRS) at rest (resting muscleV̇O2) and immediately following a maximal exercise test (post-exercise muscleV̇O2). Exercise-related increase in muscleV̇O2 (ΔmV̇O2) was derived from these measurements and cardio-pulmonary peakV̇O2 measured by analysis of expired gases. All measurements were repeated within 3 weeks of participants completing following the marathon and marathon completion time recorded. MuscleV̇O2 was positively correlated with cardio-pulmonary peakV̇O2 (r=0.63, p<0.001). MuscleV̇O2 increased at follow-up (48% increase; p=0.004) despite no change in cardio-pulmonary peakV̇O2 (0% change; p=0.97). Faster marathon completion time correlated with higher cardio-pulmonary peakV̇O2 (rpartial=-0.58, p=0.002) but not muscleV̇O2 (rpartial=0.16, p= 0.44) after adjustment for age and sex (and adipose tissue thickness for muscleV̇O2 measurements). Skeletal muscle metabolic adaptions occur following training and completion of a first-time marathon; these can be identified non-invasively using NIRS. Although the cardio-pulmonary system is limiting for running performance, skeletal muscle changes can be detected despite minimal improvement in cardio-pulmonary function.